Energy Utilization for Ground Water Pumping under Declining Water Table Scenario: A Review - Singh, Kuldeep; Sidhpuria, M. S.; Jhorar, R. K.; Kumar, Anil; Singh, Jogender; Mehla, Mukesh Kumar (International Journal of Economic Plants, 2021)
Land and water are the most essential natural resources for sustaining life. Availability of these valuable resources for our future generations depend on decisions and efforts we make today. Groundwater nearly accounts for 61.1% of the net irrigated area in India. Farmers are growing water intensive crops and using water injudiciously, following the traditional irrigation practises. This results in declining water table which in turn results in reduced well discharge, need of replacing the centrifugal pumps with submersible pumps and higher energy consumption. There is an urgent need to address these issues related to energy utilization in ground water pumping for judicious use of natural resources for sustainable agriculture and for betterment of farming community. Farmers should adopt modern irrigation management practices like drip and sprinkler irrigation for efficient use of water. Adoption of latest technologies introduced in agriculture can increase water saving during irrigation and higher crop productivity. For present study, several components associated with energy utilization in ground water pumping were reviewed viz. effect of over extraction of ground water on declining water table, mechanical factors affecting overall groundwater pumping efficiency and influence of irrigation methods and agricultural practices on energy and water consumption for ground water pumping.